New Onset of Chronic Diseases and Changes in Lifestyle Risk Factors Among Gulf War Veterans: A Longitudinal Comparison of High and Low Symptom Reporters. Issue 8 (August 2016) - Gwini, Stella M.; Kelsall, Helen L.; Ikin, Jil F.; Sim, Malcolm R.; McFarlane, Alexander C.; Forbes, Andrew B.
Abstract : Objective: The aim of this study was to compare new chronic diseases onset and longitudinal changes in lifestyle risk factors between Gulf War veterans with different symptom reporting. Methods: Data were collected from Gulf War veterans over two periods, and participants were grouped according to baseline symptom reporting. Logistic, nominal, and ordinal regressions were used for between-group comparisons. Results: The veterans comprised low, moderate, and high symptom reporters. New onset of sleep apnea [odds ratio (OR) = 9.49; 95% confidence interval (CI) = 3.48 to 25.86], musculoskeletal (OR = 8.70; 95% CI = 4.17 to 18.17), psychological (OR = 5.36; 95% CI = 2.46 to 11.70), and cardiovascular (OR = 3.86; 95% CI = 1.33 to 11.23) conditions was elevated in high versus low symptom reporters. Although odds of obesity and alcohol use increased over time and smoking halved, the changes were similar across groups. Conclusions: These findings show increasing obesity and alcohol use, and indicate that high symptomatology among veterans may predict future disease onset. Abstract : Supplemental Digital Content is available in the text